2016
DOI: 10.1177/0271678x16647737
|View full text |Cite
|
Sign up to set email alerts
|

Brain oxygen saturation assessment in neonates using T2-prepared blood imaging of oxygen saturation and near-infrared spectroscopy

Abstract: Although near-infrared spectroscopy is increasingly being used to monitor cerebral oxygenation in neonates, it has a limited penetration depth. The T 2 -prepared Blood Imaging of Oxygen Saturation (T 2 -BIOS) magnetic resonance sequence provides an oxygen saturation estimate on a voxel-by-voxel basis, without needing a respiratory calibration experiment. In 15 neonates, oxygen saturation measured by T 2 -prepared blood imaging of oxygen saturation and nearinfrared spectroscopy were compared. In addition, these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…[1][2][3] A recent study showed that NIRS-derived regional cerebral saturation (rScO 2 ; %), which is a mixture of venous (∼75%), capillary (∼5%), and arterial saturation (∼20%), correlates well with magnetic resonance imaging (MRI)determined cerebral oxygenation. 4 Further, combining NIRSmonitored rScO 2 with simultaneous mean arterial pressure can be used as a clinical tool to assess and trend cerebral autoregulation in both premature and term neonates. 5,6 A recent multicenter interventional study, the SafeboosC Study, demonstrated that cerebral oxygenation was quite stable and mostly within the expected reference ranges (55-85%) in 166 extremely preterm neonates during the first 72 h of postnatal life when rScO 2 was monitored.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] A recent study showed that NIRS-derived regional cerebral saturation (rScO 2 ; %), which is a mixture of venous (∼75%), capillary (∼5%), and arterial saturation (∼20%), correlates well with magnetic resonance imaging (MRI)determined cerebral oxygenation. 4 Further, combining NIRSmonitored rScO 2 with simultaneous mean arterial pressure can be used as a clinical tool to assess and trend cerebral autoregulation in both premature and term neonates. 5,6 A recent multicenter interventional study, the SafeboosC Study, demonstrated that cerebral oxygenation was quite stable and mostly within the expected reference ranges (55-85%) in 166 extremely preterm neonates during the first 72 h of postnatal life when rScO 2 was monitored.…”
Section: Introductionmentioning
confidence: 99%
“…Near infrared spectroscopy (NIRS) is a non-invasive tool to continuously measure regional tissue oxygenation at the bedside. It can be useful in critically ill neonates as a trend monitor to evaluate the balance between tissue oxygen delivery and consumption, providing cerebral and somatic oximetry values, and allowing earlier identification of hemodynamic changes and brain perfusion abnormalities (1,2). Sensor placement on the forehead easily allows for measurement of regional cerebral oxygen saturation (rScO 2 ) and values have been validated with jugular venous saturations in neonates (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, brief or low amplitude seizures may be difficult to identify on the compressed tracing. Newer aEEG devices have seizure detection software, which may facilitate seizure detection (2,9). The use of two channel EEG has improved seizure detection accuracy, and persistent pathological background activity has been associated with poor neurodevelopmental outcome in infants with hypoxicischemic encephalopathy (HIE) and in the preterm population (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…While S v O 2 is ideal for true OEF estimation, the QUIXOTIC uses a limited blood pool and suffers from low SNR. The low SNR, in particular a concern in paediatric populations, can be improved by including the entire cerebral blood pool as in the recently proposed "T 2 -prepared Blood Imaging of Oxygen Saturation" (T 2 -BIOS) approach (Alderliesten et al, 2016;Petersen et al, 2012). The T 2 -BIOS sequence measures pure blood T 2 (T 2b ) on a voxel-by-voxel basis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work, including our own, demonstrate that oxygen metabolism related parameters have relatively low regional variability throughout the brain. (Alderliesten et al, 2016;J. B.…”
mentioning
confidence: 99%